2015
DOI: 10.1016/j.profoo.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Extract Durian (Durio zibethinus L.) Seed Gum as an Emulsifier in Vegan Mayonnaise

Abstract: Durian is the most popular seasonal fruit in Indonesia. Only 1/3 of durian is edible, whereas the seeds are thrown away. This waste is potential of value-added such as seed gum. Mayonnaise is o/w emulsion based product use egg yolk as an emulsifier, but in this research, durian seed gum (2,5%, 3%, 3,5%, 4%, and 4,5%) has been used to replace on egg yolk in making vegan mayonnaise. The best formulation of vegan mayonnaise from 4% durian seed gum was compared to commercial and the control as well. This result is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 11 publications
5
28
2
Order By: Relevance
“…Cornelia and others () obtained a Hue ( h ) angle of 50.39 for mayonnaise with durian seed gum, well below that found in this work. Huang and others () verified that the color parameters ( L * , a * , and b * ) of mayonnaises are significantly different ( P < 0.05) when they are made with frozen egg yolk and fresh egg yolk.…”
Section: Resultscontrasting
confidence: 41%
See 2 more Smart Citations
“…Cornelia and others () obtained a Hue ( h ) angle of 50.39 for mayonnaise with durian seed gum, well below that found in this work. Huang and others () verified that the color parameters ( L * , a * , and b * ) of mayonnaises are significantly different ( P < 0.05) when they are made with frozen egg yolk and fresh egg yolk.…”
Section: Resultscontrasting
confidence: 41%
“…Chicken egg yolk contains complex compounds which are essential for the formation of an emulsion, such as phospholipids and lecithin. Most of the time, commercial mayonnaise protein content tends to be lower because other components are added into the formulation (Cornelia and others ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also no significant difference (p < .05) between the mayonnaise sample containing 75% of GA and control at the end of storage which ranging from 87.75 to 88.50%, respectively. Cornelia, Siratantri, and Prawita (2015) reported that Duran seeds gum had high emulsion stability at pH 3 when applied to mayonnaise by 4% as an egg substitute. Therefore, to obtain the maximum visco-elasticity and stability of mayonnaise, Krishnamurthy and Witte (1996) indicated that the pH range for commercial mayonnaise should be near to the iso-electric point (3.6-4.0) of the egg yolk.…”
Section: Emulsion Stability %mentioning
confidence: 99%
“…However, there are several studies have been reported to take advantage the waste of this tropical fruit. Durian seed has been reported to be capable as the emulsifier in the making of vegan mayonnaise (Cornelia et al, 2015); as the low cost hydrocolloid source from its extracted gum (Amid and Mirhosseini, 2012); as the source of biodegradable film production (Pimpa et al, 2012); to improve materials as composited with polypropylene and high density polyethylene (Osman and Zakaria, 2012); source of b-galactosidase for dairy products production (El-Tanboly, 2001); and as stabilizer substance for water in oil in water emulsion based form its conjugated whey protein isolate (Tabatabaee Amid and Mirhosseini, 2014). Meanwhile, durian rind has been reported to be beneficial in immobilization supporting material for probiotic strains (Teh et al, 2009); in wastewater treatment as biosorbent with high capacity (Kurniawan et al, 2011); in biocomposite reinforcement with polylactic acid (Manshor et al, 2014); and as main biomaterial in a new particleboards production for walls and ceiling insulation purposes (Khedari et al, 2003).…”
Section: Durian Biomassmentioning
confidence: 99%